A Study of Edible Cutleries by Using Sorghum Flour - Kabir, Mohd Hafizalrisman; Hamidon, Nuramidah (Progress in Engineering Application and Technology, 2021)
Plastic cutlery may be a convenient alternative, catastrophic to the environment, and detrimental to health. The presence of toxins and carcinogens that can quickly be ingested into the body is a petroleum by-product. As toxins and carcinogens can leech into food through the natural ecosystem, the processing of plastic cutlery has become harmful for the environment as plastics consume plenty of space and clog the landfills annually. The notion of biodegradable cutlery has been seeded by the recent ban on plastics and by the threat to the environment. While India has only seen 1 big edible cutlery entrepreneur, many other suppliers will emerge with time and demand. This research helps us to understand that consumers are aware of the harmful effects of plastic disposable cutlery use. The researcher, therefore, wishes to come up with edible cutleries that do not affect the ecosystem. The goal of this study is to raise awareness of the environmental effects of the use of plastic cutlery. Therefore, to create the edible cutleries, the investigator tests the mixture of sorghum flour, wheat flour and rice. Since it is made from natural sources, it is known as entirely degradable. The investigator prepared three samples in this study to produce the edible cutleries to observe which samples will produce better edible cutleries. By using steel cutlery, the product is formed. The samples are then tested for water absorption and soil burial examination. For commercialized purposes, to get the same shape, edible cutlery should be properly moulded and some flavor can be applied to it depending on customer demand.